Laser Noncontact Measurement Method for Elliptical Arc-toothed Cylindrical Gear - Zhou Ye; Song Aiping; Zhao Kunpeng; Yu Chenwei (Jixie chuandong)
Aiming at the lack of measurement methods for ellipsoidal arc-toothed cylindrical gears， a precision measuring device based on laser displacement sensor for elliptical arc-toothed cylindrical gear is designed. The geometric shape feature of the elliptical arc-toothed cylindrical gear is expounded， the composition and measurement principle of the laser non-contact measuring device are introduced， and the contour data model of the gear measuring section is established by laser measurement of the multiple radial cross-section profiles of the gear. The coordinate transformation of the cross-section contour data model is carried out to calculate the pitch deviation of the middle section of the gear. The tooth profile measurement data of different sections of the same tooth are analyzed， the coordinate values of the intersection points of the different section index circle and the tooth profile are calculated， and the overall deviation of the elliptical arc tooth is calculated. The method can effectively fill the measurement technology blank of the curved toothed cylindrical gear， and has high measurement accuracy and efficiency; it is also suitable for other cylindrical gear measurement.